Molecular Basis for Natural Vegetative Propagation via Regeneration in North American Lake Cress, Rorippa aquatica (Brassicaceae). (25th October 2019) - Amano, Rumi; Nakayama, Hokuto; Momoi, Risa; Omata, Emi; Gunji, Shizuka; Takebayashi, Yumiko; Kojima, Mikiko; Ikematsu, Shuka; Ikeuchi, Momoko; Iwase, Akira; Sakamoto, Tomoaki; Kasahara, Hiroyuki; et al.
Abstract: Some plant species have a striking capacity for regeneration in nature, including regeneration of the entire individual from explants. However, due to the lack of suitable experimental models, the regulatory mechanisms of spontaneous whole plant regeneration are mostly unknown. In this study, we established a novel model system to study these mechanisms using an amphibious plant within Brassicaceae, Rorippa aquatica, which naturally undergoes vegetative propagation via regeneration from leaf fragments. Morphological and anatomical observation showed that both de novo root and shoot organogenesis occurred from the proximal side of the cut edge transversely with leaf vascular tissue. Time-series RNA-seq analysis revealed that auxin and cytokinin responses were activated after leaf amputation and that regeneration-related genes were upregulated mainly on the proximal side of the leaf explants. Accordingly, we found that both auxin and cytokinin accumulated on the proximal side. Application of a polar auxin transport inhibitor retarded root and shoot regeneration, suggesting that the enhancement of auxin responses caused by polar auxin transport enhanced de novo organogenesis at the proximal wound site. Exogenous phytohormone and inhibitor applications further demonstrated that, in R. aquatica, both auxin and gibberellin are required for root regeneration, whereas cytokinin is important for shoot regeneration. Our results provide a molecular basis for vegetative propagation via de novo organogenesis.